The Impact of Socially Responsible Investment on Human Resource Management: A Conceptual Framework - Waring, Peter (Journal of business ethics, 2004)
Socially responsible investment (SRI) has increasingly assumed a major role in global equity markets. In this article we argue that the continued growth in investors seeking to align their ethical concerns with their investment strategies may influence the way in which the employment relationship is managed in publicly-listed corporations. After tracing the historical development of SRI, its implications for the conduct of human resource management (HRM) are examined. We conclude by analysing a number of the key problems associated with investor confidence in SRI funds and present a range of suggested techniques for improving screening methodologies.